Moderate Islamic Fundamentalism: Understanding the Political Thinking of the Partai Keadilan Sejahtera (PKS) - Firman Noor (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2007)
This article proposed the term moderate fundamentalism, as a tool in understanding the defining characteristic of the PKS. In short, the term refers to fundamentalism in a moderate perspective, enabling moderate fundamentalists to be involved in political activities adaptively and without resorting to the use of radical means. Using this term, I argue that the PKS is a part of the fundamentalist faction, differentiating it in principle from other modernist groups or parties in Indonesia. Its moderate nature, however, also differentiates it from the radical camps within the fundamentalist faction. The use of the term moderate fundamentalism allows for the observation of diversity within the fundamentalist faction and contributes to new insights into present-day Indonesian Islamic political parties.DOI: 10.15408/sdi.v14i3.546